The Effect Of Effleurage Massage On The Decrease In Pain Intensity In Patients In The First Stage Of Labor In The Pmb Working Area Of The Kepenuhan Community Health Center. - Heny Sepduwiana; Nur Oktapia Lestari; Yuyun Bewelli; Andriana (CV. AFDIFAL MAJU BERKAH, 2025)
Childbirth often involves significant pain, which can negatively affect maternal well-being and labor progress. Effleurage massage, a simple non-pharmacological technique, has shown potential in reducing labor pain through stimulation of endorphin release. This study aims to evaluate the effect of effleurage massage on decreasing pain intensity during the first stage of labor among mothers in the Kepenuhan Community Health Center area. The research employed a quantitative pre-experimental design with pre-test and post-test on 15 primigravida women in the active phase of labor. Data were collected using pain scales and analyzed with a paired t-test. The results indicated a significant reduction in pain scores, with mean pain decreasing from 8.33 (SD=1.345) before massage to 6.20 (SD=1.082) after massage (p<0.05). It is concluded that effleurage massage effectively reduces labor pain during the active phase. This intervention can be recommended as an economical, safe, and non-invasive method to improve maternal comfort during labor. Further research with larger samples and control groups is necessary to strengthen these findings.